The Effectiveness of HOTS-Oriented Educational Game Media to Improve Students' Science Literacy on the Material of Weather Changes on Earth - Sari, Ni Komang Desy Artika Sari; Astawan, Gede Astawan; Ni Ketut Desia Tristiantari (International Journal of Elementary Education, 2024)
The low level of scientific literacy among elementary school students poses a significant challenge in science learning, particularly on the topic of weather changes on Earth. Poor scientific literacy hinders students from understanding natural phenomena and applying scientific concepts in daily life. One proposed solution is the development of instructional media that can enhance higher-order thinking skills (HOTS) and scientific literacy. This study aims to examine the effectiveness of HOTS-oriented educational game media on improving the scientific literacy of fifth-grade elementary school students. This research employs a Research & Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The effectiveness of the media was tested through a quasi-experimental design with a Non-equivalent Control Group Design. The research sample consisted of 61 students from classes VA and VB, divided into control and experimental groups. Data collection instruments included multiple-choice tests designed to measure students' scientific literacy. The analysis results show that the use of HOTS-oriented educational game media significantly improved the scientific literacy of students in the experimental group compared to the control group. This improvement reflects the students' ability to understand the concept of weather changes on Earth and apply it scientifically. Therefore, the educational game media is deemed effective for use in fifth-grade science learning and can be widely implemented to support the development of students' scientific literacy.